AAV-PHP.eB transduces both the inner and outer retina with high efficacy in mice - Humphries, Peter; Farrar, Gwyneth (My University, 2022)
Recombinant adeno-associated virus (AAV) vectors are one of the main gene delivery vehicles used in retinal gene therapy ap proaches; however, there is a need to further improve the effi cacy, tropism, and safety of these vectors. In this study, using a CMV-EGFP expression cassette, we characterize the retinal utility of AAV-PHP.eB, a serotype recently developed by in vivo directed evolution, which can cross the blood-brain barrier and target neurons with high efficacy in mice. Systemic and intravi treal delivery of AAV-PHP.eB resulted in the high transduction efficacy of retinal ganglion and horizontal cells, with systemic delivery providing pan-retinal coverage of the mouse retina. Subretinal delivery transduced photoreceptors and retinal pigment epithelium cells robustly. EGFP expression (number of transduced cells and mRNA levels) were similar when the retinas were transduced systemically or intravitreally with AAV-PHP.eB or intravitreally with AAV2/2. Notably, in pho toreceptors, EGFP fluorescence intensities and mRNA levels were 50–70 times higher, when subretinal injections with AAV-PHP.eB were compared to AAV2/8. Our results demon strate the pan-retinal transduction of ganglion cells and extremely efficient transduction of photoreceptor and retinal pigment epithelium cells as the most valuable features of AAV-PHP.eB in the mouse retina.
PUBLISHED
Keywords: mouse retina; adeno-associated virus (AAV); gene delivery vehicles; AAV-PHP.eB; AAV2/2; AAV2/8; EGFP; Eye; Gene therapy; Mouse; Retina; Retinal degeneration